Impact of Human Diffusion and Spatial Heterogeneity on Transmission Dynamics of Mosquito-borne Diseases - Mui, Cynthia Lian Kon; Jane, Labadin (2015)
Mosquito-borne diseases are of tremendous public health concern. To study and enhance the understanding of these infectious diseases, we present a reaction-diffusion generic model for mosquito-borne diseases. It is significant that a model can be generalized for mosquito-borne diseases. One of the objectives of mathematical models is to identify factors which contribute to the spread of diseases. The traveling wave front is examined and the minimum spread speed is acquired numerically. We analyze the impact of human random movement and spatial heterogeneity on the dissemination of disease through numerical simulations. It is shown that the increment of human diffusion decreases the basic reproduction number. However, spatial heterogeneity in transmission of disease contributes to the upsurge of infection.